Triglyceride to high-density lipoprotein cholesterol ratio is associated with diabetes incidence in non-obese individuals with normoglycemia: a retrospective cohort study based on individuals from East Asia - Huang, Zhenhua; Zhang, Xigang; Sun, Dayong; Yu, Ke (Frontiers in Endocrinology, 2024)
Background Although several studies have explored the association between the triglyceride to high-density lipoprotein cholesterol ratio (TG/HDL-c) and diabetes risk, most of these studies are cross-sectional and typically involve small sample sizes, limiting the ability to draw causal inferences. Additionally, there is currently a few studies specifically focusing on non-obese individuals. Consequently, we conducted a retrospective cohort study to investigate the impact of TG/HDL-c on the risk of developing diabetes among non-obese, normoglycemic individuals across East Asian countries. Methods This secondary retrospective cohort study recruited 85,029 non-obese individuals with normal glycemic levels from East Asian countries (China and Japan). We employed Cox proportional hazards regression models, incorporating cubic splines function for smooth curve fitting and using two-piecewise Cox regression for threshold effect analysis, to evaluate the nonlinear associations between baseline TG/HDL-c ratios and diabetes risk in non-obese individuals with normoglycemia. In addition, A range of subgroup and sensitivity analyses were performed to confirm the robustness of our results. Results Among the individuals included, the average age was 42.14 ± 11.88 years, and 37,944 participants (44.62%) were male. After adjusting for covariates, the study revealed a significant correlation between the TG/HDL-c ratio and the risk of diabetes among non-obese individuals (HR=1.37, 95%CI: 1.22-1.54). Furthermore, a non-linear correlation was observed between the TG/HDL-c ratios and the incidence of non-obese diabetes, with an inflection point of 1.36. Under this threshold, the TG/HDL-c ratio notably boosts diabetes risk in non-obese populations, with an HR of 2.38 (95% CI: 1.57-3.59). Conversely, beyond the critical juncture, the upsurge in diabetes risk seems to level off, displaying no significant variation, with an HR of 1.18 (95% CI: 0.98-1.41). Conclusions This study reveals a non-linear association between the TG/HDL-c ratios and the likelihood of diabetes in non-obese individuals from East Asia. Maintaining a ratio of TG/HDL-C below 1.36 significantly reduces diabetes risk. However, once the ratio of TG/HDL-C exceeds 1.36, reducing it does not substantially lower diabetes onset risk.